Relatório de Estágio Profissional " Ser Professor de Educação Física: O Sonho tornado realidade" - Luís Carlos Machado Monteiro (2017)
With all the acquired knowledge, theoretical and practical, being applied in a teaching facility in real situations, the Professional Internship presents itself as the peak of the initial graduation. In order to respond to the challenges and demands of the teaching job, the intern starts developing professional skills that promote a critic and reflexive role by completing designated tasks and through being part of the scholar community. The current Internship Report seeks to portray the journey through the school year and it's divided in seven chapters: the first, "Introduction" contextualizes the document. The second, "Personal Framing", makes a brief presentation of my sports experience, academic decisions and events that lead me here. Next up, "Institutional Framing" characterizes the context in which the internship is held as well as it's understanding, the Internship Core, the Resident Class and the Shared Class. Following the last there's the fourth chapter, "Operational Framing" which is split in three areas. Area 1 - Learning and Teaching Organization and Management, reflects about the conception, planning, application, instruction and evaluation of the teaching process; Area 2 - School Active Role and Community Relationship presents the activities in which I took part throughout the year and the relationships I established with the scholar community; Area 3 - Professional Development portrays the aspects which contributed to my development. Chapter five refers to the study "Research Study" conducted throughout 12 weeks. Chapter six "Conclusions and Future Perspectives" focuses on a general reflection about the importance of this Professional Internship. Lastly chapter seven is dedicated to the "Bibliography".